2019
DOI: 10.1007/s13753-019-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Social Vulnerability (Re-)Assessment in Context to Natural Hazards: Review of the Usefulness of the Spatial Indicator Approach and Investigations of Validation Demands

Abstract: While social vulnerability assessments (SVA) use spatial indicators and indices that have become state of the art, they also receive substantial critique. This article analyzes, by means of a literature review of 63 articles, if and in which aspects such an indicator approach is regarded as useful by scientific studies. The findings indicate a need for more research on the validation and justification of indicators. This article supports the conceptual development of SVA by adding to reflection about advanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 83 publications
(52 reference statements)
0
39
0
1
Order By: Relevance
“…SAGE is a multinational study examining the health and well-being of adult populations and the ageing process [ 29 ]. Evaluation of the health effects of the mandatory salt reduction policy [ 30 ] on South African adults is being conducted using a nested study design in waves 2 and 3 [ 31 ]. Inclusion criteria for urine collection were: respondent must be part of the WHO-SAGE cohort, with no indication of urinary incontinence or another condition that could impede 24 h urine collection; and if female, not menstruating, pregnant, or breast feeding on the day of collection.…”
Section: Methodsmentioning
confidence: 99%
“…SAGE is a multinational study examining the health and well-being of adult populations and the ageing process [ 29 ]. Evaluation of the health effects of the mandatory salt reduction policy [ 30 ] on South African adults is being conducted using a nested study design in waves 2 and 3 [ 31 ]. Inclusion criteria for urine collection were: respondent must be part of the WHO-SAGE cohort, with no indication of urinary incontinence or another condition that could impede 24 h urine collection; and if female, not menstruating, pregnant, or breast feeding on the day of collection.…”
Section: Methodsmentioning
confidence: 99%
“…Age [15,16,18,[26][27][28][29][30][31][32][33] Gender [1,15,16,27,30,32,[34][35][36][37][38][39][40][41] Race and ethnicity [16,18,39,41,42] Occupation [15,27,31,43,44] Population growth and mortality [18,28,31,32,43,45,46] Social and economics characteristics Socioeconomic status (income, political power, prestige) [15][16][17][18]27,28,33,34,39,…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Commercial and industrial development [16,43,44] Rural/urban [16,28,54,55] Residential property [15,18,28,31,[42][43][44]50] Renters [15,18,31,33,41,43,45,50] Family and social structure [16,18,34,43,45,46] Public resource provision and public security…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…First, despite much over-lap in their formulations and end goals, there isn't a clear way to compare what indices are comprised of or actually measuring (Gillespie-Marthaler, Nelson, Baroud, & Abkowitz, 2019). Second and related, there is a lack of objective justification for the use of one indicator over another, which has reasonably led to a proliferation unproven indicators in the field (Fekete, 2019;Gillespie-Marthaler et al, 2019). Lastly, indices themselves are also questionable in their abilities to predict disaster outcomes that would intuitively align with notions of community vulnerability and resilience; Bakkensen et al (2017) found that indices have mixed results when compared to expected outcomes of property damage, fatalities, and disaster declarations.…”
Section: Introductionmentioning
confidence: 99%